Microeconomic issues of labor markets in developing countries analysis and policy implications - Mazumdar, Dipak 1932- (EDI seminar paper (Washington, D.C. : 1988), 1989)
This paper deals with labor market structures in developing countries and the impact of government policies on rural and urban labor markets. The central concern in analyses of employment is absorption of labor. Governments try to influence the demand for labor so that more members of the labor force are absorbed into productive employment. Employment outcomes are often the by-products of government policies that affect economic growth as a whole. This paper concentrates on factors that influence the structure and functioning of labor markets. In Chapter 1, a schematic picture of labor markets is presented. Chapters 2 and 3 analyze the salient features of the workings of rural and urban labor markets and discuss some important government policies that affect the functioning of these markets. The paper concludes that Government intervention in both rural and urban labor markets has often been less than successful, sometimes because their policies were based on incorrect assumptions. At other times, these policies have achieved less because the government also adopted other policies that tended to contradict the goal of providing jobs.